Injury Frequency and Location Comparison of Full Time and Part Time SWAT Operators - Fredella, Kaylee; Rodriguez, Jackeline; Wagner, Matthew; Labhart, Jake; Bunn, Jennifer (International Journal of Police Science, 2024)
Special weapons and tactics (SWAT) teams are primarily classified into two categories full-time (FT) and part-time (PT). FT teams generally work in heavily populated areas, where they are assigned to the SWAT unit with no other collateral duties. PT teams work in less populated/rural areas, with SWAT as their secondary role, and their primary duties are generally outside of SWAT. This study examined differences in injury locations, mechanisms, treatment, and length of injury time between PT and FT SWAT operators. Participants (PT n=48, FT n=24) completed a survey related to areas injured, length or injuries, mechanism of injuries, and care sought. There were group differences for percentage of injuries seeking medical assistance (FT: 25-50%, PT: 1-24%, p=0.009) and number of injuries sustained while on a live operation (FT: 1-24%, PT: none, p=0.008). There were no differences for number of injuries sustained during law enforcement career (FT: 3.1±2.5 injuries, PT: 2.40±2.2 injuries, p=0.238), number of body areas with extended pain (FT: 2.6±2.3 areas, PT: 1.9±1.8 areas, p=0.120), or time of sustained injury (both groups: 1-6 months, p=0.187). Lower back was the highest reported injured area (47%), followed by neck (14%). FT operators sustain more serious injuries than PT operators and FT operators experience more injuries while on duty. Law enforcement agencies and clinical practitioners should consider collaborating to provide FT operators with the appropriate care for their injuries. Appropriate care may effectively reduce recovery time for injuries and reduce the number of missed workdays for the operator.